Power ultrasound in organic synthesis: moving cavitational chemistry from academia to innovative and large-scale applications - Cravotto, Giancarlo; Cintas, Pedro (Chemical Society reviews, 2006)
Ultrasound, an efficient and virtually innocuous means of activation in synthetic chemistry, has been employed for decades with varied success. Not only can this high-energy input enhance mechanical effects in heterogeneous processes, but it is also known to induce new reactivities leading to the formation of unexpected chemical species. What makes sonochemistry unique is the remarkable phenomenon of cavitation, currently the subject of intense research which has already yielded thought-provoking results. This critical review is aimed at discussing the present status of cavitational chemistry and some of the underlying phenomena, and to highlight some recent applications and trends in organic sonochemistry, especially in combination with other sustainable technologies. (151 references.).